Evaluating OPAC interface alternatives for the National Library Board. - Yeo, George Kwang Hwang. (2008)
People are constantly searching for information. Information is very important to every aspect of the society. Library, being the repository of information since the early days, is sought after by many users in search of different types of information and materials. The Online Public Access Catalogue (OPAC) is paramount to the users in order to access the huge resources resided in the library. The needs for OPAC to evolve towards the users’ demand for ease and effective search are not to be ignored by libraries, as there is a host of Web-search engines and commercial databases readily available. Providing effective information access and gateway for library users is one of the National Library Board (NLB) goals. In order to assess the usefulness and usability of the available search solutions in the industry on accessing a plethora of resources, a Proof-of-Concept (PoC) is mooted to find and establish whether they are able to fit into the library users’ information search and discovery requirements.